Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. It's 100% free, no registration required.

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have some problems with the following differential equation, it looks a little bit confusing (because of notation), but please take a short look at it, it should be not too difficult.

$y'(t)=f(y(t)), t>0$ for $y\in C^1([0,\infty];\mathbb R^2)$ with $f\in C^1(\mathbb R^2; \mathbb R^2)$. $y_0$ is zero of $f:f(y_0)=0$. The real part of all eigenvalues of the matrix $df(y_0)$ is smaller or equal 0.

Now I have two things:

(i) I introduce $z:C^1([0,\infty]$ which is given by $z(t)=y(t)-y_0$. This should somehow satisfy $z'(t)-Az(t)=\xi (z(t))$, where $lim_{x->0}\frac{\xi (x)}{||x||}=0$ and $A\in GL(2,\mathbb R^2)$

but I do not see why. I tried to rewrite $z'(t)-Az(t)=y'(t)-A(y(t)-y_0)=f(y(t))-A(y(t)-y_0)$ but still do not see the relationship.

(ii) Every solution of $z'(t)-Az(t)=\xi (z(t))$ should satisfy $z(t)=\sum_{i=1}^{2}(z_i(0)z_h^{(i)}(t)+\int_{0}^{t}\xi_i(z(s))z_h^{(i)}(t-s) ds)$

with $z_h^{(i)}$ i=1,2 solutions of the equation $z'_h(t)=Az_h(t)$ with starting values $z_h^{(1)}=(1,0), z_h^{(2)}=(0,1)$

If you could tell how the solution of the differential equation looks like, it should be no problem to see that it satifies the equation above.

share|cite|improve this question
up vote 2 down vote accepted

It looks you're deriving the variation of constants formula. Here its statement,

Let $X(t)$ be a fundamental solution matrix of the differential equation $\dot{x}(t) = Ax(t) + h(t)$. Then general solution is $x(t) = X(t)[X^{-1}(t_0)x(t_0) + \int_{t_0}^t X^{-1}(s)h(s)ds]$. Where $X(t)$ has linearly independent solutions of $\dot{x} = Ax$ as its columns.

(i) Let A be the jacobian of $f$ at $y_0$. Then $\dot{z}(t) - Az(t) = f(y(t)) - A(y-y_0) = f(y_0) + Df(y_0) (y - y_0) + O(|y - y_0|^2) - A(y - y_0) = O(|y - y_0|^2) = O(|z|^2).$.

(ii) We have $\dot{z}(t) - Az(t) = \xi(z(t))$. Multiply both sides by inverse of fundamental matrix $Z^{-1}(t)$. Use fact that $Z^{-1}(t)$ is a solution of the adjoint equation $\dot{z}(t) = -z(t)A$. Then $Z^{-1}(t)\dot{z}(t) - Z^{-1}(t)Az(t) = Z^{-1}(t)\xi(z(t)) = \frac{d}{dt}[Z^{-1}(t)z(t)] = Z^{-1}(t)\xi(z(t))$. Which yields the variation of constants formula. Then doing the matrix multiplication should give you your answer.

Does this help you? I'm not using your terminology, but I can if you'd like me to.

share|cite|improve this answer
Thank you, I just completet the second part. – Alexander Nov 23 '12 at 13:25

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.